Uniform initial 10Be/9Be inferred from refractory inclusions in CV3, CO3, CR2, and CH/CB chondrites - Dunham, Emilie T.; Wadhwa, M.; Desch, S. J.; Liu, Ming-Chang; Fukuda, K.; Kita, N.; Hertwig, Andreas; Hervig, R. L.; Defouilloy, C.; Simon, S. B.; Davidson, J.; Schrader, D. L.; et al. (Geochimica et cosmochimica acta, 2022)
Short-lived radionuclides (SLRs) once present in the solar nebula can be used as probes of the formation environment of our Solar System within the Milky Way Galaxy. The first-formed solids in the Solar System, calcium-, aluminum-rich inclusions (CAIs) in meteorites, record the one-time existence of SLRs such as 10Be and 26Al in the solar nebula. We measured the 10Be-10B isotope systematics in 29 CAIs from several CV3, CO3, CR2, and CH/CB chondrites and show that all except for a FUN CAI record a homogeneous initial 10Be/9Be with a single probability density peak at 10Be/9Be = 7.4 × 10-4. Integrating these data with those of previous studies, we find that most CAIs (81%) for which 10Be-10B isotope systematics have been determined, record a homogeneous initial 10Be/9Be ratio in the early Solar System with a weighted mean 10Be/9Be = (7.1 ± 0.2) × 10-4. This uniform distribution provides evidence that 10Be was predominantly formed in the parent molecular cloud and inherited by the solar nebula. Possible explanations for why unusual CAIs (FUNs, PLACs, those from CH/CBs, and those irradiated on the parent body) recorded a 10Be/9Be ratio outside of 7.1 × 10−4 include the following: 1) They incorporated a component of 10Be that was produced in the nebula by irradiation; 2) they formed after normal CAIs; and 3) they were processed (post-formation) in a way that affected their original 10Be signatures. Given the rarity of these examples, the overall uniformity of initial 10Be/9Be suggests that Solar System 10Be was predominantly inherited from the molecular cloud.
Die Zahlen "10" und "9" sind bei "10Be/9Be" hochgestellt
Gesehen am 08.07.2022